Magnetic Resonance Imaging and Neuropsychological Correlates of Subcortical Vascular Dementia - Paul, Mohd Altaf (Asian J Neurosurg, 2018)
Common understanding of dementia is mostly based on the Alzheimer's disease model. However, in subcortical vascular dementia (SVaD), several other cognitive and behavioral dysfunctions predominate over what is commonly noticed in Alzheimer's disease. There are inconsistencies in literature regarding the profile of cognitive impairments in vascular dementia. OBJECTIVE: In the current study, different cognitive functions pertaining to different lobes of the brain along with neuropsychiatric symptoms we explored in a holistic manner. MATERIALS AND METHODS: A sample of 12 patients diagnosed with SVaD without any comorbidity were recruited for the study. All the patients underwent magnetic resonance imaging (MRI) scanning and different standardized neuropsychological tests were administered. RESULTS: Patients reported various neuropsychiatric symptoms with varied severity, mostly falling in moderate range, reflecting organic personality change. Most of the cognitive functions pertaining to different lobes of the brain were impaired with parietal lobe being intact mostly. Comparison of MRI findings and neuropsychological findings revealed that there is involvement of cortical functions with the impairment in subcortical structure. CONCLUSION: These findings emphasis need to look beyond clinical diagnosis and MRI findings for better rehabilitation of the patients by including cognitive dysfunction as well as emotional disturbances prominent in SVaD which might me quite distressing for caretakers.